]Optimization of Forms of Educational Activities in the Classroom Music as a Condition of Development of Creative Activity of Younger Schoolboys - Chuang, Guan (Pedagogical Discourse, 2015)
The problem of optimizing forms of educational activity of younger schoolboys at music lessons as a condition of their creative activity has been studied. Creative activity is the desire to use new techniques in solving this problem, search for ways to overcome the difficulties, the need for making novelty items in the job means. Creative activity describes the ability of the individual identify the problem and find the means to solve it, desire to seek new ways to perform academic tasks, the ability to apply knowledge in new situations. Creative activity not a single trait, the property of the individual, and integrative quality characteristics of the individual. Creative activity is dependent on the age of the specific and fully defined it. Primary school age especially prone to creativity in all its manifestations. It is pertinent to this age when creativity we mean such activities, which resulted in acquired something new, original, in varying degrees, expresses individual inclinations, abilities and individual experience of younger pupils. And the novelty of the process and its results while optional is objective, it can be generally subjective, is only one new. For the development of creative activity it is important to create the pedagogical conditions that allow more fully meet the interests and develop the creative abilities of students. One of these conditions is the use of music lessons on various musical forms of educational activities in their optimal combinations. This is possible only if clearly define the different forms and combinations. Revealed the notion of frontal, group and individual work as a form of educational activity of younger schoolboys at music lessons. Under the form of educational activity refers somehow ordered structure of educational and musical activities of students, due to the goals, objectives, logic and methods of music education and education for each stage of the learning process.